High-resolution analyses of the secretomes from murine C2C12 cells and primary human skeletal muscle cells reveal distinct differences in contraction-regulated myokine secretion - Förster, Pia Marlene; Hogenkamp, Julian; Pottgießer, Moira Fee; Binsch, Christian; Humpert, Awovi Didi; Brügge, Carolin Laura; Deatc, Michelle Isabel; Ensenauer, Regina; Chadt, Alexandra; Thoresen, G. Hege; Ouwens, D. Margriet; Hartwig, Sonja; et al. (Frontiers in Physiology, 2025)
Myokines released by skeletal muscle in response to contraction may contribute to the health-promoting effects of exercise. Previous studies with cultured rodent and human myotubes have revealed highly complex patterns of myokine secretion. However, the commonalities and differences in the secretory response of the different cell models have not been explored, limiting the interpretation of these results. In the present study, we performed a comprehensive analysis of contraction-regulated secretomes using the most commonly used skeletal muscle cell models, cultured murine C2C12 myotubes and satellite cell-derived primary human myotubes (HSkMC). The cells were subjected to low-frequency electrical pulse stimulation (EPS) for 6 h followed by high-resolution mass spectrometry analysis of secreted proteins in the culture medium. We identified 5,710 and 3,285 proteins in the secretomes of C2C12 myotubes and HSkMC, with 80% of human myokines also detected in the murine secretome. Additionally, we found 518 and 336 secreted proteins that were differentially regulated during contraction in murine and human cells, respectively, along with 1,440 and 385 previously unknown potential myokines secreted by murine and human myotubes. Bioinformatic prediction analyses revealed that the majority of the newly identified myokines were secreted via unconventional protein secretion pathways (UPS) in the murine secretome, whereas most novel proteins in the human secretome were secreted via the classical endoplasmic reticulum (ER)-to-Golgi pathway. Moreover, ontology analysis indicates cell type-specific differences in cellular compartments involved in myokine secretion. Collectively, our results provide a comprehensive overview of the secretomes of two of the most commonly used cell models and may provide guidance for further studies of myokines.